THE EFFECT OF FIRM COMPETITIVE ADVANTAGE CREATIONS ON BEYOND SUFFICIENCY-ECONOMY CONSUMPTION BEHAVIORS - Rattanaprakarn, Chanchai; Samutachak, Bhubate; Piboolsravut, Priyanut (Ph.D. in Social Sciences Journal, 2017)
No abstract available